2023
DOI: 10.3390/molecules28020519
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Enzymatic Hydrolysis Using Flavourzyme Enzyme on Functional, Secondary Structure, and Antioxidant Characteristics of Protein Hydrolysates Produced from Bighead Carp (Hypophthalmichthys nobilis)

Abstract: In the current study, bighead carp fish were used in conjunction with the flavourzyme enzyme to obtain (FPH) fish protein hydrolysates. The optimum conditions of the hydrolysis process included an enzyme/substrate ratio of 4% and a temperature of 50 °C and pH of 6.5. The hydrolysis time was studied and investigated at 1, 3, and 6 h, and the (DH) degree of hydrolysis was recorded at 16.56%, 22.23%, and 25.48%, respectively. The greatest yield value was 17.83% at DH 25.48%. By increasing the DH up to 25.48%, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…Comparison with the "Brenda" enzyme database at NCBI for Bacillus subtilis suggested the presence of other enzymes in the electrophoretic bands. The fourth band (37 kDa) could correspond to both endopeptidase La (EC 3.4.21.53) and subtilisin (EC 3.4.21.62), consistent with previous research identifying a metalloprotease (37 kDa) in B. subtilis [42]. Additionally, bands with molecular weights of approximately 27 and 29 kDa were observed, consistent with previous studies of proteases from Bacillus strains, typically ranging from 28 to 70 kDa [43].…”
Section: Molecular Sizes Determinationsupporting
confidence: 91%
“…Comparison with the "Brenda" enzyme database at NCBI for Bacillus subtilis suggested the presence of other enzymes in the electrophoretic bands. The fourth band (37 kDa) could correspond to both endopeptidase La (EC 3.4.21.53) and subtilisin (EC 3.4.21.62), consistent with previous research identifying a metalloprotease (37 kDa) in B. subtilis [42]. Additionally, bands with molecular weights of approximately 27 and 29 kDa were observed, consistent with previous studies of proteases from Bacillus strains, typically ranging from 28 to 70 kDa [43].…”
Section: Molecular Sizes Determinationsupporting
confidence: 91%
“…Similarly, the antioxidant activity determined through the DPPH method was more than 50-times higher in the case of FPH flour compared to that of WF (294.00 mg Trolox/100 g vs. 5.17 mg Trolox/100 g). Similar results regarding TPC values were reported by Sharma et al [59] and Alahmad et al [60].…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…Increased enzyme concentrations consistently led to reduced ash content, emphasizing the vital roles of these factors in determining the samples' ash content (Table 2 ). This change in ash content in hydrolysate products could be attributed to the enzymatic breakdown of chemical bonds between organic and inorganic components, facilitated by the protease enzyme employed in the enzymatic process, as highlighted by Alahmad et al ( 2023 ). Moisture content analysis showed that hydrolysate powders had significantly higher moisture content compared to SYRB (Table 2 ; P ≤ 0.05).…”
Section: Resultsmentioning
confidence: 94%
“…Longer incubation times and enzyme concentrations lead to more pronounced changes in lightness and color difference, attributed to the Maillard reaction involving amino acids and reducing sugars (Arsa and Theerakulkait 2015 ). Color values may be linked to enzymatic hydrolysis conditions, including reaction time and the type of protease enzyme (Alahmad et al 2023 ). Additionally, the combined effect of prolonged incubation and increased enzyme concentration may lead to synergistic interactions, amplifying the impact on polyphenol and flavonoid transformations and resulting in a more pronounced color shift.…”
Section: Resultsmentioning
confidence: 99%